(untitled) (Journal of the College of Basic Education, 2023)
Any plan, including educational plans, no matter how much effort was spent in preparing it and providing it with the requirementsits success will depend on the human element and its ability to exploit it, and onTherefore, educational plans should aim at preparing experts, cadres, and human elements to achieveIts goals, and then the goals of national development, including the administrative cadres in a way that suits the spirit of the times.And the major transformations in our general life and the building requirements for the future.(The Ministry of Education, 1983, pg. (62).The educational administrative cadres in the apparatus that participate effectively in setting the policyeducational and activities that achieve this policy and includes all educational authorities advisoryand the executive, including the school administration, which received great attention in educational studies because of itsOf an important role and prominent effects in the success of the educational process(Salmani and others - 1987 - p.).The principal of the secondary school is responsible for leading all the efforts and forces that he or she experiences.Within the framework of his work and directing it to achieve the desired goals, and he is responsible for the progress of business inschool in terms of its effectiveness and progress, in addition to its responsibility in providing and preparing allThe necessary facilities for the educational process. The principal of the school is not limited to managing affairsthe administrative school in a monotonous manner, but rather combines in his work the administrative and technical aspects together, just as theHis humanitarian work aims to provide the available conditions and capabilities that help to achieveeducational goals